Using DEA in conjunction with designs of experiments: an approach to assess simulated futures in the Afghan educational system. Issue 4 (1st November 2016) - Marlin, B; Sohn, H
Abstract: This research presents an assessment of the simulated futures of the Afghan educational system. We use a hybrid analytical process combining simulation, design of experiments, and data envelopment analysis (DEA) that is capable of studying the dynamic behaviour of the Afghan educational system. By using the process, we are able to determine the critical relationships, potential futures, and unforeseen consequences of potential policies regarding primary and secondary education in Afghanistan. This research also provides insight into the use of DEA when applied to a large-scale discrete event social simulation.